Morphological and endoscopic diagnostic criteria of serrated adenomas of the colon - Nechipay, A. M.; Zobnina, M. V.; Cherkasova, L. M.; Perfilyev, I. B.; Krivopuskov, V. A. (Rossiĭskiĭ zhurnal gastroėnterologii, gepatologii, koloproktologii, 2016)
The aim of review. To generalize literature data on endoscopic and morphological diagnostics of serrated adenomas of the colon. Key points. In 2010 a new variant of histological classification of colonic tumors have been accepted by WHO, according to which serrated neoplasms were defined as separate group of preneoplastic changes, along with colonic adenomas. At the present time hyperplastic polyps and other serrated neoplasms are considered to be precursor lesions for 15 to 20% of sporadic or asymptomatic colorectal cancers located mainly in proximal colon, that progress by specific serrated adenoma-related pathway. Diagnostics of such lesions both on microscopic and macroscopical levels is associated with significant difficulties due to absence of the uniform nomenclature, definite morphological features and endoscopic semiotics. Conclusion. Definition of main morphological and endoscopic diagnostic criteria of all types of serrated adenomas will provide successful diagnostics along with differentiation with other epithelial colonic lesions that is required for proper choice of management approach.